Peningkatan derajat putih tepung apel malang menggunakan pengering vakum (Vacuum Drying) untuk mendapatkan suhu dan waktu pengeringan terbaik - Puji Putro Ardianto; Lorine Tantalu; Sri Handayani; Sudirman Sudirman (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
The purpose of this study was to increase the whiteness in the process of making apple flour so that it can be used as a base for making various kinds of food preparations. The treatment are comparing the best temperature and time, which each of them will be used in different times, namely 2 hours, 4 hours, 6 hours and 8 hours. This study used a ran-domized block design method (RAK) which was arranged in two factors, namely factor 2. And for temperature (T): 50˚C (T1), 55˚C (T2), 60˚C (T3), 65˚C (K4). The results of data analysis using ANOVA for all parameters showed significant differences. For the highest mean value for yield, whiteness, amylose and amylopectin content, crude fiber content was 14.50% respectively (at treatment temperature of 50oC with 2 hours drying time); 78.50% (at treatment temperature of 60oC with a drying time of 2 hours); 55.29% (at a temperature treatment of 65oC with a drying time of 8 hours); and 18.26% (at a tempera-ture treatment of 50oC with a drying time of 2 hours). Meanwhile, the lowest water con-tent value is at an average value of 17.46% at a temperature treatment of 65oC for 8 hours. The best treatment to produce apple flour with the best parameter value was ob-tained in the treatment with a temperature of 55oC with a drying time of 2 hours.